(3TQM GdaGVd GdLhGO Ydi UajMI GdCSWQdGHs - (3LhGO Hf SYO Hf LOGO GdHZOGOj GdcGXei hjYQa HGdaGVd GdLhGO , J (B1065 (3g`s; (3eMeO Hf GdMSf Hf Rjf GdOjf GdehShj GdYGedj , GHf GdTgjO GdKGfj,J (B1030 (3g` s ((3GdSeGhI s)
(3ChdgG (B:s
(3JYGdJ OQLGJ bOSc hHYO, ajbhd deG cGf Yde GdCSWQdGH ef Hjf GdYdhe GdQjGVjI hcGfJ GdQSGdI GdeSeGI HGdUajMI eMJGLI Edi TQM s
(3BNQgG (B:s
(3hHYO eG YQaJ Cf GdhLg GdePchQ LGQ eY GdGNJdGa ai GdWhd ShGA GJabG ai GdYQV ChdG jXgQ dc LQjGf GdMce ai LejY GdCbSGe GdSJI hMjK GfJgi cdGe GdeUfa adfbWY GdcdGe MGeOjf Gddg s
(3Vef eLehY s
(3HgG fXGe GdJYbjHIs
(3jbhd GdfGSN Gfg fbdgG ef fSNI eZdWI LOkGs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B89 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B191s
Keywords: (3Gdadcs